Planteamiento De Un Sistema De Prefiltrado A Través De Mallas Geotextiles En Procesos De Ósmosis Inversa: Una Solución Para La Salinización En Cuerpos De Agua Costeros. (2020)
Salinization in water bodies is a widely discussed topic and with an even wider range of variables, it can be natural, due to the geology of the terrain or the climate, or anthropogenic, that is, generated by man through industrial and mining activities, by the action of dumping, agricultural waste, among others. Historically, the first known desalination plant dates from the time of Thales of Miletus and Democritus who commented that fresh water was obtained by filtering seawater through the land. Much later, in the 60's of the last century, the discovery of the technique that would revolutionize the entire desalination process took place: reverse osmosis, a system that, due to its efficiency and high performance, is currently the most used in the world. Today, there is a production of more than 24 million cubic meters of desalinated water per day throughout the world, supplying more than 100 million people. In Colombia, salinization affects a remarkable amount of water bodies, a special affected is the Magdalena River, because of the intrusion of the sea on the Mallorquin swamp, this situation has a negative influence on the quality of life of the population, intervening equally in the poor development of flora and fauna. Thus, this research addresses the main benefits and disadvantages of geotextile meshes, along with their application in reverse osmosis, the important treatments to ensure their optimal functioning and how it could be preliminarily developed, an alternative solution to mitigate and subsequently eliminate, the salt intrusion in the marsh of Mallorquin.